Awareness and Knowledge of Common Eye Diseases Among the Academic Staff (Non-Medical Faculties) of University of Malaya - Chew, Y.K.; Reddy, S.C.; Karina, R. (Malaysian Medical Association, 2004)
A cross sectional study was conducted to assess the level of awareness and knowledge of common eye diseases (cataract, glaucoma, diabetic retinopathy and refractive errors) among 473 academic staff (non-medical faculties) of University Malaya. The awareness of cataract was in 88.2%, diabetic retinopathy in 83.5%, refractive errors in 75.3% and glaucoma in 71.5% of the study population. The knowledge about all the above common eye diseases was moderate, except presbyopia which was poor. Multivariate analysis revealed that females, older people, and those having family history of eye diseases were significantly more aware and more knowledgeable about the eye diseases. Health education about eye diseases would be beneficial to seek early treatment and prevent visual impairment in the society.